THE CONNECTION OF PHYSICAL EDUCATION WITH OTHER SUBJECTS (Scientific journal of the Fergana State University, 2024)
This article reveals issues related to the physical education of preschool children, which widely consider the forms of organization of physical education, physical culture and educational activities, sports games and training issues, the purpose and objectives of physical education and general principles, principles of health orientation, the importance of environmental factors as a means of physical education, information about power the qualities of children, speed, dexterity, endurance and flexibility, as well as ways and means of their development.